1988
DOI: 10.1056/nejm198803173181101
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of Gonococcal and Chlamydial Ophthalmia Neonatorum

Abstract: We evaluated the use of silver nitrate drops and tetracycline ointment for the prophylaxis of ophthalmia neonatorum in a controlled trial involving 2732 newborns in Nairobi, Kenya. The overall rates of prevalence of intrapartum maternal gonococcal and chlamydial infection were 6.4 and 8.9 percent, respectively. After prophylaxis with silver nitrate, the incidence rates of gonococcal, chlamydial, and nongonococcal, nonchlamydial ophthalmia neonatorum were 0.4, 0.7, and 6.2 percent, respectively, whereas after p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(52 citation statements)
references
References 19 publications
1
49
0
2
Order By: Relevance
“…550 In another study, tetracycline ointment was superior to silver-nitrate drops. 541 conclusions. Evidence for the benefit of prophylaxis with silver-nitrate drops, tetracycline ointment, or erythromycin ointment to prevent ophthalmia neonatorum is well established, based largely on developed-country studies.…”
Section: Prevention and Treatment Of Ophthalmia Neonatorummentioning
confidence: 91%
See 3 more Smart Citations
“…550 In another study, tetracycline ointment was superior to silver-nitrate drops. 541 conclusions. Evidence for the benefit of prophylaxis with silver-nitrate drops, tetracycline ointment, or erythromycin ointment to prevent ophthalmia neonatorum is well established, based largely on developed-country studies.…”
Section: Prevention and Treatment Of Ophthalmia Neonatorummentioning
confidence: 91%
“…539 In developing countries such as Kenya, where rates of maternal STDs are high, rates of gonococcal ophthalmia range from 15% to 34%. 540,541 A variety of interventions have been evaluated for prevention of ophthalmia neonatorum in developed countries, mostly in hospital settings, and have largely focused on the prevention of gonococcal infections. [542][543][544][545] These studies have suggested that silver-nitrate, tetracycline, or erythromycin ointments given prophylactically are equivalent in efficacy.…”
Section: Prevention and Treatment Of Ophthalmia Neonatorummentioning
confidence: 99%
See 2 more Smart Citations
“…No entanto, esses agentes não se mostraram mais eficazes contra a CT que o NP, pelo menos quando utilizados da mesma maneira, ou seja, em aplicação única (12,(49)(50)(51)(52) . Além disso, os antibióticos citados levaram à geração de resistência bacteriana e à consequente ocorrência de epidemias, relacionadas com germes resistentes, como estafilococos (53,54) .…”
Section: Profilaxia Da Cn No Brasil E No Mundounclassified